Analysis of Customer Satisfaction in Construction Companies Using QFD Method - Suhada, Dharma; Syairuddin, Bambang (Institut Teknologi Sepuluh Nopember, 2020)
The study adapted the QFD model as main framework for analyzing service quality by using of service quality dimensions (tangibility, reliability, responsiveness, assurance, and empathy. The research used the questionnaires that were distributed between twenty respondents who are the consumers of that company. The survey analyzed the consumers’ needs of houses and the ways for improving the quality of services. The outcomes of the study display that the top priority for customer satisfaction, such as name the suitability of the project report with actual conditions in the field; Ability to complete within deadlines; Service level after completion; Application of work procedures and instructions for completing projects; Project workers' expertise in using equipment in the field; Level of trust in communication follow-up; Discipline and compliance with agreed project schedules and Fulfillment of construction functions. While the technical response given by the company to increase consumer satisfaction are Monitoring the results of reports with the field by Project Control; Training of contractor field supervisors; Monitoring the communication system periodically; Training in the use of work equipment; Periodic S curve monitoring; Improved technical communication between the person in charge with the representative of the employer; Periodic SOP briefing; and Giving reward and punishment to Project Managers and Field Teams.